The impact of the Financing structure of the framework of the pecking order theory in firm value: Analytical study of a sample of industrial companies listed in the Iraqi Stock Exchange for the period (2004-2019) - Hussein Shiaa Al Salami, Hussam; Abbas Hussain AL Sharifi, Karrar (Iraqi Journal for Administrative Sciences, 2024)
The current study aims to show the impact of the financing structure within the framework of the pecking order theory as an independent variable in enhancing the firm value as a dependent variable, Companies, the study adopted a time series of 2004-2019. And on a set of financial indicators for the financing structure according to the theory of the study, and a set of statistical methods represented in simple linear regression, t-test, f-test and coefficient of determination R2, using the programs (Excel2019) and (SPSSV.26), and the study came out with a set of conclusions, the most important of which are the economic and security conditions that Iraq is going through and these factors have obstructed the capture of funding sources and imposed a lot of difficulties in obtaining appropriate funding sources. Available investment opportunities.